Comparing high-throughput methods to measure antibody dependent cellular cytotoxicity during HIV infection - Mbodo, Iyaloo (Division of Virology, 2017)
The prevalence of HIV-1 is highest in Sub-Saharan Africa. Protective immune responses directed against HIV are complex and involve both cellular and humoral immunity. Based on the recent finding that the best correlate of protection against the first protective prophylactic RV144 vaccine were HIV-specific antibody responses, including those mediating natural killer (NK) cell antibody-dependent cellular cytotoxicity (ADCC), there has been considerable interest in measuring alternative roles for HIV-specific binding antibodies. The aim of this MSc dissertation was to optimise and compare two high-throughput flow cytometry based approaches - the GranToxilux and PanToxilux assays - to measure HIV-specific ADCC responses. To do this, NK cells from a panel of healthy HIV-negative individuals were screened for their ability to directly kill the tumour cell line K562, as a measure of direct NK cell cytotoxicity. The individual with the highest granzyme B and caspase activity against K562 cells was chosen as the universal NK cell donor for this study.